GENDER AND EDUCATIONAL BACKGROUND AS FACTORS INHIBITING TEACHING OF ARABIC LANGUAGE IN SENIOR SECONDARY SCHOOLS IN KWARA STATE - Sanusi, Taofeeq Olamilekan; AbdulGaniy, Ibrahim Solahudeen Owoyale; Rafiu, Jamiu Abdur (STAI Nurul Huda Kapongan Situbondo, 2024)
The study examined the factors preventing the teaching of Arabic in senior secondary schools in Kwara State. The population was 23,458, and a sample of 379 students was selected using Kredjcie and Morgan's table. Multistage sampling procedures were used with purposive sampling to select three Local Government Areas (LGAs) and stratified sampling for seven LGAs. Simple random sampling was used to select 30 public schools, 10 from each LGA. The Adapted Gender and Educational Background as Inhibiting Factors of Teaching Arabic Language Questionnaire (GEBALQ) was used for data collection. The instruments were validated and reliability tested through pilot testing with 40 senior secondary school students. The study used a T-retest method and correlation statistics to analyze the impact of gender and educational background on teaching Arabic in senior secondary schools in Kwara State. The results showed that gender did not significantly inhibit teaching Arabic, while educational background significantly inhibited it. The study concluded that both male and female Arabic language teachers should put more effort and commitment into teaching the subject, as their overall teaching of Arabic language is subpar. Additionally, the study recommended that Arabic language teachers should undergo training and re-training to improve their proficiency in Arabic script, dialects, grammar, vocabulary, pronunciation, calligraphy, and literature. Overall, the study highlights the need for improved teaching methods and support for both male and female Arabic language teachers in Kwara State.